COMPETITIVENESS OF SOYBEAN BUSINESS FARMING ANALYSIS IN GROBOGAN REGENCY CENTRAL JAVA PROVINCE - Nurul Widya Anggraeni; Wiludjeng Roessali; Hery Setiyawan (AGROLAND: The Agricultural Sciences Journal, 2018)
Soybean is one of the strategic commodities. To fulfill the increasing of domestic demand, it must be supplied from imports because domestic production is unsufficient. In addition, lower price of imported soybean has effected in competition of domestic farmers to get profit. Demand of soybean in the international and domestic market has always increased. Indonesia has imported soybeans to fill domestic soybean demand. This condition will have an impact on the decline in farm income due to soybean import. The aims of this study were to analyze the level of private profitability and competitiveness of soybean farming in Grobogan Regency.This research used survey research method with number of samples taken through simple random sampling of 100 soybean farmers. Data were analyzed by Policy Analysis Matrix (PAM). The results showed that private profitability of soybean farming in Grobogan Regency was Rp1.690.393,22 per MT. Two indicators to measure the competitiveness were Private Cost Ratio (PCR) and Domestic Resources Cost Ratio (DRCR). PCR value was 0,75 which showed that soybean farming in Grobogan Regency was more competitive and Domestic Resources Cost Ratio (DRCR) showed 0,88. It showed that soybean farming had a comparative advantage.